2005
DOI: 10.1016/j.jvs.2005.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The lifetime prevalence of abdominal aortic aneurysms among siblings of aneurysm patients is eightfold higher than among siblings of spouses: An analysis of 187 aneurysm families in Nova Scotia, Canada

Abstract: There was a significant difference between the siblings of the AAA patients and those of the spouses both in the frequency of AAA detected by ultrasonography screening and in the overall prevalence of AAA. The overall prevalence of AAA in the siblings of AAA patients was about eight times that observed among the siblings of their spouses (19.2% vs 2.3%). These findings confirmed previous reports on high prevalence of AAA among siblings of AAA patients and emphasized the importance of an ultrasonography screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 32 publications
2
32
0
4
Order By: Relevance
“…1 Since then, several studies have reported a high prevalence of AAA among siblings of AAA patients, supporting that AAA is an inheritable disease. [2][3][4] In a casecontrol study of 98 AAA cases and 102 controls, a positive family history of AAA was associated with an increased risk of AAA (OR 4.77, 95% CI 1.26-18.1). 5 Similar risk rates were confirmed in a Finnish study of relatives of 150 AAA patients, but only 29% of the first-degree relatives were included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Since then, several studies have reported a high prevalence of AAA among siblings of AAA patients, supporting that AAA is an inheritable disease. [2][3][4] In a casecontrol study of 98 AAA cases and 102 controls, a positive family history of AAA was associated with an increased risk of AAA (OR 4.77, 95% CI 1.26-18.1). 5 Similar risk rates were confirmed in a Finnish study of relatives of 150 AAA patients, but only 29% of the first-degree relatives were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…1 Case series have reported increased familial risk for AAA and several studies have reported a high prevalence of AAA among siblings of AAA patients. [2][3][4] Case-control studies have shown an approximately four-fold increased risk being affected for firstdegree relatives of AAA patients. 5,6 These studies are mostly based on consecutive patient series from one or few centers, and few population-based reports covering the subject can be found.…”
mentioning
confidence: 99%
“…A recent twin study showed an estimated 70% heritability 6 and others have shown increased incidence of AAA in first-degree relatives of affected individuals 7,8 . Several studies have attempted to identify genetic risk variants.…”
mentioning
confidence: 97%
“…On the other hand, for AAA, ultrasonography screening studies have demonstrated the costeffectiveness of population-based ultrasonography screening programs and a decrease in the number of aneurysm-related deaths. 5 Several recommendations have been made, including a recent consensus statement in which Kent et al 6 recommended ultrasonography screening for AAA for all individuals aged Ͼ60 years and for those aged Ͼ50 years with family history of AAA and the recommendation by the US Preventive Service Task Force 7 to screen for AAA in men aged 65 to 75 years who have ever smoked.…”
mentioning
confidence: 99%